Ações básicas de detecção precoce e fatores de risco para o câncer de mama em mulheres atendidas em uma unidade básica de saúde Fortaleza-Ceará - Silva, Anna Paula Sousa da (2010)
The breast cancer has been established as a serious public health problem, not only by the growing number of cases diagnosed each year, but also by the financial investment that is required for diagnosis and treatment. The objective of this study was to evaluate actions for early detection and risk factors for breast cancer in women at a Basic Health Unit, Fortaleza, Ceará. It was conducted a cross-sectional study, descriptive and analytical, with a quantitative approach, on shares of early detection and risk factors to the breast cancer. The research was developed in a Basic Unit of Family Health, Fortaleza, Ceará, in the period from March to November of 2008. The population was based on the amount of annual gynecological attendances made by nurses, for a total of 1920. The sample was 320 women. It was used as technique for data collection a semi-structured interview and as instrument, the semi-structured form. For the analysis was used the chi-square test with the aid of SPSS version 15.0 in order to measure the association of variables, at 5% level of significance. The following results were obtained: the average age of interviewed women was 37, had family income below a minimum wage 139 (43.44%) of them; studied between 11 and 15 years of study, 192 (60%) of the total; reported first episode menstrual, aged over twelve years, 206 (64.38%); only 64 (20%) had entered the menopause and 238 (74.38%) had their first pregnancy, aged below 30 years of age; on breastfeeding, 210 (65.63%) breastfed their children; it was found that 177 (55.31%) make use contraceptive oral; had family history of breast cancer, 71 (22.19 %); affirm the habit of smoking 62 (19.38%); said drink alcohol 89 (27.81%). It was inferred that 252 (78.75%) know the BSE. The Clinical examination of the breasts is performed by 246 (76.87%) of respondents. It was observed that 46 (44.23%) reported perform mammography annually. It was detected that the years of study influenced on practice of BSE. However, there was a lack of association between the time of study and implementation of BCE and knowledge of mammography. As the range of income, this variable was associated only with the knowledge of the BSE and the mammography. It is noteworthy from the results of the research, that even with the technology developed in recent decades for the control of breast cancer, can not ignore the many factors that make the etiology of this neoplasm. Hence the need for greater effectiveness in detecting breast cancer, and early recognition of its risk factors